Relationship between Defense Expenditure and Economic Growth in Nepal - Poudel, Omkar (Unity Journal, 2023)
This research study investigates the impact of defense expenditure (DE) and export on Real Gross Domestic Product (RGDP) of Nepal. The RGDP is the dependent variable and defense expenditure and export are the independent variables. Data since 1974 to 2020 are taken from secondary sources of Nepal Rastra Bank, ministry of finance to find the relationship between them. Augmented Dickey- Fuller Test is run to test stationary condition in the variables. The Vector Error Correction Method (VECM) coefficient is significant and positive. There is no evidence that economic growth and the independent variables have a long-run relationship but there is short-run causality running from DE to RGDP and export to RGDP.The result of Granger Causality Test shows there exists unidirectional relationship between RGDP and DE. Similarly, there exists unidirectional relationship between RGDP and export but there is no relationship between DE and Export. Results confirm the variables are the determinants of economic growth in Nepal. So policy makers should consider on these variables for economic growth of the country.